Peningkatan Kemampuan Pemahaman Membaca Melalui Media Pembelajaran Augmented Reality - Liza Afifah Amaliah; Syibli Maufur; Inayatul Ummah (Jurnal Kajian Pendidikan dan Cakrawala Pembelajaran, 2025)
Character formation and moral development for children are not only obtained from formal institutions, but also non-formal institutions such as RTQ (Rumah Tahfidz Al-Qur'an) which have a role in forming good character. This study aims to determine the Role of RTQ (Rumah Tahfidz Al-Qur'an) Al-Muwaffaq in the Formation of Early Childhood Character in Batukaropa Village, Bulukumba Regency. This study uses a qualitative method with a descriptive approach. Data collection techniques use observation, interview and documentation techniques. Data analysis used is qualitative data analysis with data collection steps, data reduction, data presentation and drawing conclusions. Proof of data validity using triangulation techniques. The triangulation used is the combination of data sources with other data sources. The results of the study indicate that there are several roles of the Al-Muwaffaq Al-Qur'an Tahfidz House in the Formation of Early Childhood Character in Batukaropa Village, Bulukumba Regency. First, the Al-Muwaffaq Al-Qur'an Tahfidz House as a facilitator. Second, Al-Muwaffaq Al-Quran Tahfidz House as a companion and supervisor. And third, Al-Muwaffaq Al-Quran Tahfidz House as a motivator.